Furthering the Aim of Multilingualism through Integrated Terminology Development - Sibula, Pumlani M. (Lexikos, 2007)
Abstract: This article aims at giving a brief account of how the activities of the Unit for isiXhosa, one of the five units of the Stellenbosch University Language Centre, contributes to the development of integrated technical terminology lists for all departments of the University. After the reason for this terminology development has been explained, a description is given of the six trilingual terminology lists that have been compiled so far. On a discussion of the problem of finding suitable isiXhosa terminological equivalents follows an exposition of the methodology used in compiling these lists. Finally it is shown how the collaboration with various bodies benefits the Unit for isiXhosa. The article concludes by stating how these lists have been received and are made known.